Sequential Oxidation–Prins Reaction Processes Induced by the Same Iron Salt: Direct Access to 2-Aryl-4-Chloro-Tetrahydropyrans from Benzyl Alcohols - Fache, Fabienne; Muselli, Mickaël; Piva, Olivier (Synlett, 2013)
A clay-supported iron(III) nitrate (Clayfen) was used as a stoichiometric reagent to first oxidize benzylic alcohols. The aldehydes thus obtained were converted in situ into tetrahydropyrans by way of a Prins cyclization induced by iron species already present in the media.
Keywords: oxidation; benzyl alcohols; Prins cyclization; sequential reactions; iron catalysis